PROPHYLACTIC AND THERAPEUTIC EFFICACY OF THE POLYVALENT PYOBACTERIOPHAGE IN THE TREATMENT OF ACUTE DESTRUCTIVE PANCREATITIS - V. P. Nikulina; Z. M. Ozova; M. A. Godkov (Неотложная медицинская помощь)
BACKGROUND. The high mortality in severe  acute  pancreatitis is mainly assoociated with septic complications developing  during translocation of intestinal potentially pathogenic flora into the initially sterile  necrosis.AIMOFSTUDy. To determine the prophylactic and therapeutic effect of polyvalent  pyobacteriophage (PBP) included into the complex treatment of acute destructive pancreatitis to reduce the rate of infectious  complications and mortality. MATERIALANDMETHODS. The study included  38 patients admitted to the  N.V. Sklifosovsky Research  Institute  for Emergency Medicine with  acute  destructive pancreatitis and  pancreatic necrosis. All patients underwent the standard therapy. In patients of group 1 (N=13), PBP was included into treatment in the first 2 weeks after admission  (2–15  day). In patients of group 2 (N=12), the bacteriophage was used during septic complications (16–60  hours). The comparison  group consisted  of patients not receiving PBP in the course of treatment. The activity of the inflammatory process over time was evaluated by the level of C-reactive protein (CRP). The marker of systemic inflammation was procalcitonin (PCT). We performed immunology tests: the number of leucocytes, lymphocytes  (Tand B-lymphocytes), phagocytic activity and oxygen metabolism of neutrophils in the HCT-test, concentration of immunoglobulin A, M, G, circulating  immune complexes  (CICs) before and after PBP.RESULTS. It was found that  the earlier use of PBP had helped  reduce  inflammation and areas  of intoxication, which was manifested by a fall of CRP and PCT (p<0.05), lesser number of complications and mortality in patients of group 1 compared  to patients of group 2 and the comparison  group. Immunology tests  revealed  an increase  in the absolute number of T-lymphocytes, growth of IgA and IgG (p<0.05) involved in opsonization and antigen  presentation to T-lymphocytes  and affecting  the cellular  and humoral  mechanisms of immune  response to infectious  antigens.  The use of PBB in patients with infectious  complications (group 2) did not lead to a significant reduction  of necrosis zones and, as a consequence, indices of inflammation. Only CRP was significantly reduced. The analysis of immunological tests  revealed  an increase  in the number of T-lymphocytes and IgG concentration (p<0.05).CONCLUSIO N. The use  of PBP in the  treatment of acute  destructive pancreatitis in the  early stages  resulted  in sanitation of infection  foci, reduction  of the  number  of infectious  complications,  reduced  hospital stay and reduced  mortality  down to zero. The inclusion  of PBP into treatment at a later  date  after admission  did not reduce  the number  of complications,  but it contributed to activation  of immune defense  mechanisms and reduced  mortality compared  with the control group.